HUKUM PIDANA DALAM PERSPEKTIF ADMINISTRASI PUBLIK: KAJIAN ATAS PENEGAKAN HUKUM TERHADAP PELANGGARAN PERIZINAN - Bongso, Farras; Ibrahim, Arif M. (Universitas Bina Taruna Gorontalo, 2023)
This article analyzes the role of criminal law in enforcing licensing violations in the context of public administration in Indonesia. Law enforcement against licensing violations is an important part of efforts to maintain order, justice, and legal certainty in the public sector. However, the implementation of law enforcement is often faced with various challenges, including the inconsistency between existing regulations and practices in the field and the lack of synergy between law enforcement agencies and local governments. This article uses a descriptive-analytical approach by utilizing secondary data from journals, books, and related reports. The findings show that although there are already quite strict regulations related to licensing, the effectiveness of law enforcement is still limited by slow bureaucracy and lack of transparency. Therefore, this article proposes several innovative strategies to improve the effectiveness of law enforcement, including the use of information technology in licensing monitoring and increasing the capacity of law enforcement officers at the regional level.